The Role of Dozer Volunteers in the Electoral Winning Strategy of Andi Asman Sulaiman and Andi Akmal Pasluddin in the Political Contestation of Bone Regency - Hidayat, Andi Rahmat Nizar; Cahyo Nugroho, Tri (Department of Political Sciences, Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2026)
This research analyzes the role of